Programming with R - S. R. Mani Sekhar (Cengage India, 2017)
Programming with R is targeted towards people who wish to learn a new programming language, beginner in the field of data science, data analytics and people who wish to start hands-on session using RStudio.People who may get the benefit from this book are student, data scientist, and researcher. All the programs in this book are executed in RStudio environment under windows platform. The book is organized into 10 chapters. Chapter 1 covers the process of installation, running, visualization and help document of R. Chapter 2 to 4 covers basic concept of R and data structure and programming structure. Chapter 5 and 6 covers function and exception concept. Chapter 7 covers the concept of input and output management in R. chapter 8 deals with different visualization techniques. Chapter 9 and 10 covers probability and statistic concepts.